Egypt : Guiding Reform of Energy Subsidies Long-Term - Griffin, Peter; Laursen, Thomas; Robertson, James (World Bank, Washington, DC, 2016)
This paper examines the short- and long-run economic impact of Egypt's energy subsidy reform in July 2014 (without and without compensating transfers for the bottom 40 percent of the income distribution) and the decline in global energy prices, as well as the long-run impact of phasing out the energy subsidies over a 5 year period. The analysis uses a Computable General Equilibrium model with 56 productive sectors, including 11 energy subsectors. The short-run analysis employs a two-stage factor market adjustment, with wages first fixed and then flexible. The long-run analysis is run in a recursive dynamic mode, capturing the impact of improved productivity and increased investment resulting from more efficient allocation of resources and reduction in government deficits. In the short run, the 2014 reforms lead to slightly lower consumption while investment increases strongly and production shifts from highly subsidized energy-intensive sectors such as energy, water and sanitation, and transport to other sectors (notably construction). The impact on overall consumer prices is limited. In the longer run, real GDP growth increases by about one percentage point relative to the baseline before the 2014 reform.